Factors Affecting Myopia in Elementary School - Oktaviani Cahyaningsih; Dewi Sari Rochmayani (Indonesian Journal of Global Health Research, 2023)
Refractive errors are the most common visual disturbances in the world, of which myopia is the most common refractive error. Myopia can be caused by genetic and environmental factors, one of which is by doing close-up activities such as using gadgets. The use of gadgets today is very much needed in everyday life. At least 30 million children and adolescents in Indonesia use digital media as their main choice of communication channel. This study was conducted to find out what factors can affect the incidence of myopia in Darul Quran elementary school children Semarang including gender, heredity, close-range activities, outdoor activities with the research sample being all Darul Quran elementary school students who suffer from myopia. The research used is quantitative research oriented with inductive logic, data collection is done by questionnaire. With saturated sample technique, the total population and the number of samples is 90 respondents, the questionnaire used in primary data collection was carried out. Validity and reliability tests were tested on 30 respondents taken from outside the research location. The results of the study were carried out with the Chi-Square correlation test where, the highest incidence of myopia is in children with female sex as many as 33 (56.9%), there is a history of myopia as much as 27 (46.6%), melee activity < 5 jam many as 25 (43.1%) and outdoor activities < 5 jam sebanyak 25 (43.1%). The incidence of myopia that is most related and influential sequentially is heredity, melee activity, gender and outdoor activities.